Character education in the folklore of South Kalimantan (the perspective of literary sociology) - Haswinda Harpriyanti; Kamariah Kamariah (SOCIA: Jurnal Ilmu-Ilmu Sosial, 2019)
This study is focused to reveal character education in the folklore of South Kalimantan. the matter will be examined in this study are: (1) How character education that relate to yourself?; (2) How character education that relate to our fellow humans?; and (3) How character education related to the environment?; The methods used in this research is descriptive analysis method. The techniques used for data collection are the techniques of exploration.The data in this study is a collection of the folklore of the South Kalimantan, published by Lembaga Pendidikan Banua Banjarmasin, the mold is second in 2006 and third in 2008 mold. The result of this study is there are few of character education values mentioned, divided by three object: that relate to yourself (hard work, curious, responsible, independent, entrepenuer,); relate to our fellow human beings (obedient, social care, democratic); and relate to the environment (care for the environment).